2016 IEEE International Conference on Communications (ICC) 2016
DOI: 10.1109/icc.2016.7511009
|View full text |Cite
|
Sign up to set email alerts
|

Improper Gaussian signaling in full-duplex relay channels with residual self-interference

Abstract: We study the potential employment of improper Gaussian signaling (IGS) in full-duplex cooperative settings with residual self-interference (RSI). IGS is recently shown to outperform traditional proper Gaussian signaling (PGS) in several interference-limited channel settings. In this work, IGS is employed in an attempt to alleviate the RSI adverse effect in full-duplex relaying (FDR). To this end, we derive a tight upper bound expression for the end-to-end outage probability in terms of the relay signal paramet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Consider the optimization problem in (8) and simplify it by rewriting the first constraint in terms of α using the the monotonic increasing characteristic of the logarithmic function in the objective function obtaining equivalent optimization problem…”
Section: Theoremmentioning
confidence: 99%
See 1 more Smart Citation
“…Consider the optimization problem in (8) and simplify it by rewriting the first constraint in terms of α using the the monotonic increasing characteristic of the logarithmic function in the objective function obtaining equivalent optimization problem…”
Section: Theoremmentioning
confidence: 99%
“…On the other hand, IGS scheme achieves superior rate improvements for systems not supported with interference cancellation techniques and deal with interference as noise. IGS scheme is employed in different interference scenarios such as two user single input single output interference channel [6], k-user multiple input single output interference channel [7], full duplex relaying [8], alternate relaying [9] and underlay cognitive radio [10]- [16].…”
Section: Introductionmentioning
confidence: 99%
“…Similar DoF results were derived for the four-user interference channel in [14]. After that, a number of new works has emerged, and the payoffs of improper signaling have been revealed for different multiuser scenarios such as the interference channel [3][4][5]15], Z-interference channel [6,[16][17][18], broadcast channels with linear precoding [19,20], underlay and overlay cognitive radio networks [7,8,21] and relay channels [22,23]. More recently, in [24], the authors showed the advantages of improper signaling in a multiuser scenario where a point-to-point link coexists with a multiple access channel.…”
Section: Introductionmentioning
confidence: 51%
“…They found that, while PGS provided 1 DoF, 1.2 DoF were achievable by IGS. A great deal of works has followed these lines showing the payoffs of IGS for different interference-limited networks, such as the IC [6]- [8] (also with discrete modulation schemes in [9]), the Z-IC [10]- [13], broadcast channel treating interference as noise [14], [15], underlay and overlay CR [16]- [20], relay channels [21], [22], etc.…”
Section: Introductionmentioning
confidence: 99%